Resonant X-ray emission spectroscopy of liquid water: Novel instrumentation, high resolution, and the “map” approach - Weinhardt, Lothar; Fuchs, O.; Blum, M.; Bär, M.; Weigand, M.; Denlinger, J. D.; Zubavichus, Yan; Zharnikov, Michael; Grunze, Michael; Heske, C.; Umbach, E. (Journal of electron spectroscopy and related phenomena, 2010)
Techniques to study the electronic structure of liquids are rare. Most recently, resonant X-ray emission spectroscopy (XES) has been shown to be an extremely versatile spectroscopy to study both occupied and unoccupied electronic states for liquids in thermodynamic equilibrium. However, XES requires high-brilliance soft X-ray synchrotron radiation and poses significant technical challenges to maintain a liquid sample in an ultra-high vacuum environment. Our group has therefore developed and constructed a novel experimental setup for the study of liquids, with the long-term goal of investigating the electronic structure of biological systems in aqueous environments. We have developed a flow-through liquid cell in which the liquid is separated from vacuum by a thin Si3N4 or SiC window and which allows a precise control of temperature. ...